If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + 4) + 2bi = 6 + -5ib Reorder the terms: (4 + a) + 2bi = 6 + -5ib Remove parenthesis around (4 + a) 4 + a + 2bi = 6 + -5ib Solving 4 + a + 2bi = 6 + -5bi Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + a + -4 + 2bi = 6 + -4 + -5bi Reorder the terms: 4 + -4 + a + 2bi = 6 + -4 + -5bi Combine like terms: 4 + -4 = 0 0 + a + 2bi = 6 + -4 + -5bi a + 2bi = 6 + -4 + -5bi Combine like terms: 6 + -4 = 2 a + 2bi = 2 + -5bi Add '-2bi' to each side of the equation. a + 2bi + -2bi = 2 + -5bi + -2bi Combine like terms: 2bi + -2bi = 0 a + 0 = 2 + -5bi + -2bi a = 2 + -5bi + -2bi Combine like terms: -5bi + -2bi = -7bi a = 2 + -7bi Simplifying a = 2 + -7bi
| x+5=51 | | 26b=832 | | 15hc=-12 | | 4x-46=32-2x | | 2m+10+3m=180 | | y=-40x^2+1100x | | -y-7=-4 | | 3x^5-5x^3+15=0 | | 2*(x-3)=(x-1)+7 | | 4+16a= | | (a+4)+2bi=6-5i | | 3x+y=y+90 | | 8n-7(-6n-2)=-33+3n | | 22w=726 | | 2x^4+16x^2+32x=0 | | 3*(x+2)=-5-2*(x-3) | | 8y+-3x=20 | | 20-28x=132 | | 8y+-4y= | | 20y-17x=55 | | 2x-2(7x+12)=2(x+3) | | 8w+3-2w-8=6w-5 | | X+5+7x-2= | | 2x-2(7x+12)=2(x-3) | | 3.2p=52.5 | | y-14.6=-31.7 | | 3(4*-9)=23 | | 5-4x+10= | | 9=1/3p | | 2r+(-5+r)=13+2r | | 4b^2+40b=0 | | 7+4=7 |